2013
DOI: 10.2460/javma.242.11.1544
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of risk factors for development of corneal ulcer after nonocular surgery in dogs: 14 cases (2009–2011)

Abstract: Several risk factors were identified for development of corneal ulcers after nonocular surgery was performed with general anesthesia in dogs. Perioperative eye protection strategies and postoperative ophthalmic examination are needed to reduce the occurrence of corneal ulcers and their progression, especially for high-risk dogs and procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 31 publications
1
21
0
1
Order By: Relevance
“…The prevalence of 1% dogs with corneal ulceration post‐GA in the current prospective study is comparable to the prevalence of 1.9% in the only other veterinary study published to date, which was retrospective and found that lengthy procedures or spinal surgery increased the risk of corneal ulceration . The current study identified none of the risk factors assessed, including length of anesthesia, to be associated with corneal ulcerative disease.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The prevalence of 1% dogs with corneal ulceration post‐GA in the current prospective study is comparable to the prevalence of 1.9% in the only other veterinary study published to date, which was retrospective and found that lengthy procedures or spinal surgery increased the risk of corneal ulceration . The current study identified none of the risk factors assessed, including length of anesthesia, to be associated with corneal ulcerative disease.…”
Section: Discussionsupporting
confidence: 74%
“…The current study identified none of the risk factors assessed, including length of anesthesia, to be associated with corneal ulcerative disease. However, comparisons between Park's study, which had a patient population of 14 animals, and the present study are difficult, as the current study represents a much larger patient population (100 dogs and 199 eyes) and is prospective rather than retrospective . Moreover, the Park study did not report if there were pre‐existing ocular diseases.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This is a complication that has been reported to occur more commonly in neurosurgeries (Park and others 2013). All cases undergoing a general anaesthesia at the centre where the patient underwent surgery are submitted to a simple prophylactic ocular lubricating protocol to help protect their corneas.…”
Section: Discussionmentioning
confidence: 97%
“…Superficial corneal ulceration was a common short‐term complication postoperatively with two cases occurring within the first 5 days of surgery. Corneal ulceration has been associated with general anesthesia in animals, and this may be a contributing factor with the two cases that occurred within 1 week of surgery . Some additional contributing factors may include decreased tear production, self‐trauma, delayed healing of small abrasions due to corticosteroid therapy, and reactivation of herpes virus .…”
Section: Discussionmentioning
confidence: 99%